The Lipin Family: Mutations and Metabolism - Reue, Karen (2009)
PURPOSE OF REVIEW: The family of three lipin proteins act as phosphatidate phosphatase (PAP) enzymes required for glycerolipid biosynthesis, and also as transcriptional coactivators that regulate expression of lipid metabolism genes. The genes for lipin-1, lipin-2 and lipin-3 are expressed in key metabolic tissues, including adipose tissue, skeletal muscle, and liver, but the physiological functions of each member of the family have not been fully elucidated. Here we examine the most recent studies that provide information about the roles of lipin proteins in metabolism and human disease. RECENT FINDINGS: Recent studies have identified mutations that cause lipin-1 or lipin-2 deficiency in humans, leading to acute myoglobinuria in childhood or the inflammatory disorder Majeed syndrome, respectively. The effects of lipin-1 deficiency appear to include both the loss of glycerolipid building blocks and the accumulation of lipid intermediates that disrupt cellular function. Several studies have demonstrated that polymorphisms in the LPIN1 and LPIN2 genes are associated with metabolic disease traits, including insulin sensitivity, diabetes, blood pressure, and response to thiazolidinedione drugs. Furthermore, lipin-1 expression levels in adipose tissue and/or liver are positively correlated with insulin sensitivity. Studies of lipin-1 in adipocytes have shed some light on its relationship with insulin sensitivity. SUMMARY: Lipin-1 and lipin-2 are required for normal lipid homeostasis, and have unique physiological roles. Future studies, for example using engineered mouse models, will be required to fully elucidate their specific roles in normal physiology and disease.